2001
DOI: 10.1007/s002130100728
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid receptor agonist and antagonist effects on motor function in normal and 1-methyl-4-phenyl-1,2,5,6-tetrahydropyridine (MPTP)-treated non-human primates

Abstract: Cannabinoid agonists do not induce catalepsy in primates, a finding that differs from their effects in rodents. The primate may be more suitable than rodents for predicting the effects of cannabinoids and their therapeutic potential on select primate behaviors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
0
6

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(55 citation statements)
references
References 25 publications
0
49
0
6
Order By: Relevance
“…(Mailleux and Vanderhaeghen, 1993;Di Marzo et al, 2000;Lastres-Becker et al, 2001a,b;Gubellini et al, 2002;reviewed in Brotchie, 2003;Fernandez-Espejo et al, reviewed in Brotchie, 2003;Fernandez-Ruiz and Gonzalez, 2005). Notwithstanding the above, studies using SR141716 in rat and primate models of PD or LID (Meschler et al, 2001;van der Stelt et al, 2005) provided conflicting results. Rimonabant treatment also failed to influence dyskinesia in the first small-scale, randomized, double-blind, placebo-controlled human study (Mesnage et al, 2004).…”
mentioning
confidence: 99%
“…(Mailleux and Vanderhaeghen, 1993;Di Marzo et al, 2000;Lastres-Becker et al, 2001a,b;Gubellini et al, 2002;reviewed in Brotchie, 2003;Fernandez-Espejo et al, reviewed in Brotchie, 2003;Fernandez-Ruiz and Gonzalez, 2005). Notwithstanding the above, studies using SR141716 in rat and primate models of PD or LID (Meschler et al, 2001;van der Stelt et al, 2005) provided conflicting results. Rimonabant treatment also failed to influence dyskinesia in the first small-scale, randomized, double-blind, placebo-controlled human study (Mesnage et al, 2004).…”
mentioning
confidence: 99%
“…More specifi cally, they found that CB 1 receptors in parkinsonian and MPTP-lesioned basal ganglia bind more [ 3 H]CP55940 and exhibit greater coupling effi ciency than control tissue and that these changes were less marked in the basal ganglia of MPTP-treated animals that had been exposed to L-DOPA. It is noteworthy, however, that Meschler et al 196 have reported that SR141716A does not alleviate motor defi cits induced by MPTP in cynomolgus monkeys.…”
Section: Excitotoxicity and Traumatic Brain Injurymentioning
confidence: 93%
“…The efficacy of SR 141716A administration in improving forepaw stepping in rats with unilateral 6-OHDAlesioned was demonstrated both alone and in concomitant administration with low dosage L-DOPA [44]. Nevertheless, it should be mentioned that SR 141716A administration failed to improve Parkinsonian-like symptoms in MPTP-treated in primates [34]. Mixed results were obtained in MPTP-treated rhesus monkeys were the selective CB 1 antagonist CE-178,253 was ineffective against motor disabilities except when co-administered with subthreshold doses of L-DOPA, thus enhancing the anti-Parkinsonian effects of L-DOPA treatment [45].…”
Section: The Therapeutic Potential Of Ecb-based Agents In Pd: To Boosmentioning
confidence: 99%
“…Nevertheless, the stimulation of CB 1 receptors can disclose its potential as option to reduce the impact of the disabling involuntary movements induced by protracted treatment with L-DOPA. In a recent study [34], L-DOPA-induced dyskinetic movements (LIDs) were reduced by subchronic administration of WIN 55,212-2 in rats unilaterally lesioned via 6-OHDA in the medial forebrain bundle. The stimulation of CB 1 receptors can provide an anti-excitotoxic response and a neuroprotective action via the reduction of glutamate release [36].…”
Section: The Therapeutic Potential Of Ecb-based Agents In Pd: To Boosmentioning
confidence: 99%